Assessment of antioxidant activities of an endemic species from Tunisia: Rhanterium sueaveolens Desf related to its phenolic composition. (November 2019) - Hitana, Mabrouka; Dupas, Coralie; Oulahal, Nadia; Degraeve, Pascal; Najaa, Hanen; Bouhamda, Talel; Fattouch, Sami; Neffati, Mohamed
Abstract: In the present study, the phenolic composition and the antioxidant activities of aqueous methanol extracts from the flowers, stems and roots of Rhanterium suaveolens were investigated to assess its potential as a source of promoting bioactive constituents. The identification and the quantification of phenolic compounds were assessed by HPLC-ESI-MS. A total of 24 metabolites including phenolic acids and flavonoids were identified and reported for the first time in R. suaveolens species. Chlorogenic acid and its derivates; 3.4-di-O-caffeoyquinic and 4.5- di-O-caffeoyquinic acids were identified as the major compounds in the flowers and the stems extracts. They were predominant in the roots extract but with lower amounts. On the other hand, quercetin-3-O-galactoside was found to be the major flavonoids in the studied extracts. Furthermore, results showed that the flower extracts displayed the most effective DPPH scavenger (EC50  = 0.331 ± 0.009 mg/ml) and ferric reducing power (EC1 = 0.408 ± 0.006 mg/ml). These findings support the use of R. suaveolens as a promising source of alternative bioactive ingredients for both industrial and medicinal uses. Highlights: This is the first investigation on the phenolic profile of R. suaveolens species. HPLC-ESI-MS was adopted for the identification and the quantification of phenolics in the methanolic extracts. 24 compounds were identified for the first time. Chlorogenic acid and hydrocinnamnic acids family were the most abundant compounds. The flowers extract showed the most interesting antioxidant effects.